(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Chrisnawati L, Miftahudin, Utami DW. 2025. Discovery of potential alleles for iron (Fe) toxicity tolerance in rice: Phenotypic and genotypes analysis of doubled haploid lines. Biodiversitas 26: 851-858. Tidal swamplands present a promising opportunity for expanding rice cultivation. However, iron (Fe) toxicity poses major obstacles to development. To overcome these challenges, it is crucial to develop Fe-tolerant rice genotypes and identify molecular markers, such as single nucleotide polymorphisms (SNPs). This study aimed to identify Fe-tolerant doubled haploid rice genotypes and SNP markers related to Fe toxicity tolerance. The experiment was carried out by cultivating 45 doubled haploid rice lines (BMIP 1-BMIP 33 and BMIP 39-BMIP 50), derived from reciprocal crosses between IR54/Parekaligora and Bio 110/Markuti, under Fe-toxic conditions. Phenotypic evaluations were based on the leaf bronzing symptom (LBS) score and genotype analysis was performed using high-throughput sequencing of 384 SNPs. SNPs correlated with phenotypic data were analyzed using the Tassel 2.0 software, with significance set at a p-value <0.05. The results showed that there were 12 highly Fe-tolerant and 33 lines with moderate tolerance and seven SNPs were identified in proximity to QTLs/genes associated with iron (Fe) toxicity and abiotic stress responses, namely qFETOX-2, OsIRT, OsFRO2, OsNRAMP5, and Cyclin-like F-box. Phylogenetic analysis grouped Fe-tolerant lines, including BMIP 25, BMIP 26, BMIP 46, BMIP 47, BMIP 48, BMIP 49, and BMIP 50, with Mahsuri as the positive control, showing shared genetic traits. These results provided valuable markers for breeding programs to obtain Fe-tolerant rice.